Geology and spatial distribution of uranium mineralisation in the SK anomaly area, Rossing area, Namibia - Abraham, Irene M (My University, 2010)
The nature, geology and spatial distribution of uranium minerals in the SK anomaly area, Rössing Uranium Mine, Namibia, is investigated to perceive if the mineralogy is favourable for uranium extraction using sulphuric acid plant. In addition to the SK anomaly area, the Rössing Uranium Mine area has two other uranium-rich areas, the SH and SJ anomalies. At present only the SJ anomaly area is being mined due to its favourable mineralogy of 55% uraninite, 40% secondary minerals and 5% betafite. The SK anomaly is made up of about 32 sub-anomalies, of which SK4 is part off. Geological mapping, radiation survey analyses, petrographic analyses, 3-D modelling, SEM, QEMSCAN, uranium budget and geochemical analyses have been carried out with the aim to understand the area’s geology, outline the high priority exploration targets within the SK anomaly, spatial distribution, and proportions of the primary, secondary and refractory uranium bearing minerals in the SK area. Of the different six leucogranites observed by Nex (1997) in the Goanikontes area; only four types (B to E) are found in the SK area. Betafite is associated with type D leucogranite, although traces are present in type E leucogranite. Betafite ((U,Ca)(Ti,Ta,Nb)3O9) is a Ti-rich member of the pyrochlore group and does not readily release uranium with acid, even in an oxidized state. Currently betafite cannot be leached at atmospheric pressure with sulphuric leach. Due to its high abundance in SH area, if SK area has high betafite, Rössing Uranium Mine has to come with another approach to leach the uranium out of betafite. The SJ area contains sheeted leucogranites emplaced into the Rössing Formation calc-silicates and the meta-pelitic sediments of the Khan Formation. The same geological setting is also observed in the SK area. The Rössing and Khan lithological units seem to increase in thickness from the SJ to the SK area. The bedding/foliation relationship and the relative ages of the lithological units indicate that the SK area is an anticline; while the SK4 area is a syncline. In the SK anticline, where the marble unit tripled in thickness from the SJ pit, there is 65% betafite, 8% uraninite and 27% secondary uranium bearing minerals. The SK4 area is a minor syncline within the major SK anticline area; has 5% betafite, 64% uraninite and 31% secondary uranium bearing minerals. This study concludes that there is a structural and lithological control on betafite formation in the SK anticline and SK4 areas. If the current acid plant is used to process material from the SK anticline area, recoveries will be low as most of the uranium is hosted in betafite form. In fact only U-silicates and uraninite will be leached successfully. Considering the fact that the SH area also has a high betafite content, Rössing Uranium Mine may have to find ways to leach the uranium from betafite, to make SH and SK areas feasible for mining.